The republics of Central and South America: their resources, industries, sociology and future (1922)
The purpose of this book is to provide, within the compass of a single volume, a succinct study of the Latin American republics, and their social and physical conditions; which, whilst affording exact, and, to a considerable extent, detailed information, is at the same time of interest to the general reader. There are many books of travel and description dealing with these lands, but none perhaps affording a review such as is aimed at in the present work.